THE USE OF MANTRA IN THE TRADITION OF MAITAI ALLO MACOA IN ONGLO PEOPLE CAMPALAGIAN SUBDISTRICT POLMAN REGENCY : A REVIEW OF THE SEMIOTICS - Aswad, Hajaratul; Nurhayaty, Nurhayaty; Said, Ikhwan (Universitas Hasanuddin, 2018)
The aims of this research were to decipher and to explain interaction between spell and Maitai Allo Macoa tradition, the exsistence of spell and tradition of Maitai Allo Macoa especially to sociaty in Ongko village. The content of spell is the old poem that consist of proface and cloosing. Whereas the manuscript is a creation of cultural that used the symbols and have meaning. This study was qualitative research that orient to the words in the form of spelling and the manuscript of symbols of Maitai Allo Macoa. This research was done in Ongko village sub regency Campalagian, Polman regency. The data were gained by observation, either close and open interview to society, recorded and written. The result of this research showed that the sociaty usually used the spell in the manuscript of Maitai Allo Macoa before going to wander. It consists of there kinds of spell and one manuscript; pembueang, peakkeyang, assalamakang and Maitai Allo Macoa manuscript. In general, the spelling manuscript has relationship to the Holy Al-Qur’an text. It means the creation of spelling inspired by Holy Alquran. Things that decide the good day in the manuscript are time and symbol meaning which are used as the direction to held the holy activity. The exsistence or effect on the using of the spell and tradition of Maitai Allo Macoa is success and safety.